Pesticides and respiratory symptoms among farmers - Neice Müller Xavier Faria; Luiz Augusto Facchini; Anaclaudia Gastal Fassa; Elaine Tomasi
OBJECTIVE: Despite the intensive use of pesticides in agriculture there are few studies assessing the risk of respiratory conditions from this exposure. The study aimed at quantifying the prevalence of respiratory symptoms among farmers and evaluating its relationship with occupational use of pesticides and the prevalence of respiratory symptoms. METHODS: A cross-sectional study was conducted among 1,379 farmers from two municipalities of Southern Brazil in 1996. Frequency and type of chemical exposure and pesticide poisoning were recorded for both sexes. All subjects aged 15 years or older with at least 15 weekly hours of agricultural activity were interviewed. An adapted questionnaire developed by the American Thoracic Society was used for the assessment of respiratory symptoms. Multivariate logistic regression analysis was carried out. RESULTS: More than half (55%) of interviewees were male. The prevalence of asthma symptoms was 12% and chronic respiratory disease symptoms was 22%. Higher odds ratios for both asthma (OR=1.51; 95% CI: 1.07-2.14) and chronic respiratory disease (OR=1.34; 95% CI 1.00-1.81) symptoms were found in women. Logistic regression analysis identified associations between many forms of exposure to pesticides and increased respiratory symptoms. Occurrence of pesticide poisoning was associated with higher prevalence of asthma symptoms (OR=1.54; 95% CI: 1.04-2.58) and chronic respiratory disease symptoms (OR=1.57; 95% CI: 1.08-2.28). CONCLUSIONS: In spite of causality limitations, the study results provide evidence that farming exposure to pesticides is associated with higher prevalence of respiratory symptoms, especially when the exposure is above two days per month.